Magnetic catalyst with wide pH adaptability for degrading antibiotics and preparation method of magnetic catalyst
By introducing bimetallic MOF of nickel and cobalt into the catalyst and forming a carbon protective layer through high-temperature heat treatment, the catalyst recovery problem and the problem of narrow pH range are solved, and a catalyst that is efficient, stable and easy to separate is achieved, which significantly improves the degradation efficiency of antibiotics in water bodies.
Patent Information
- Application Number
- CN202510025767.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
AI Technical Summary
Existing catalyst powders have problems in recycling in industrial applications and high requirements for use environments, especially when the pH range is narrow, the catalytic efficiency decreases or fails.
A bimetallic metal organic frame (MOF) material of nickel and cobalt is used, and a carbon protective layer is formed by high-temperature heat treatment to obtain a magnetic catalyst with wide pH adaptability. The method includes reacting in a solvent to form a nickel precursor, then reacting with cobalt salt, polyvinylpyrrolidone and dimethylimidazole to form a cobalt nickel bimetallic MOF and heat treatment in argon.
The catalyst is achieved with high catalytic activity, wide pH range stability and easy separation, suitable for large-scale industrial production, and significantly improves the degradation efficiency of antibiotics in water bodies.
Smart Images

Figure CN119746866A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of antibiotic degradation materials, and in particular to a magnetic catalyst for degrading antibiotics with broad pH adaptability and a preparation method thereof. Background Art
[0002] At present, the problem of antibiotic pollution in water bodies is becoming increasingly serious. Antibiotics in the environment mainly come from agriculture, medical treatment and household medicine. When they flow into water bodies, they will have direct or indirect impacts on the aquatic ecosystem. At the same time, the residual antibiotics and the reproduction of drug-resistant microorganisms pose a threat to human health.
[0003] In the process of removing antibiotics from water bodies, catalyst powder technology has attracted attention due to its high efficiency and environmental friendliness. Catalyst powder degrades antibiotics in water bodies through advanced oxidation technology, which oxidizes and decomposes antibiotic molecules by producing highly active free radicals (such as hydroxyl radicals OH). At present, the degradation of antibiotics in sewage bodies mostly uses iron-based catalysts, which are formed by rapid oxidation of scrap iron in a strong oxidant solution, and the main component is γ-FeOOH; it exhibits excellent catalytic activity under appropriate pH values, catalyst dosages and ozone decomposition conditions, and can significantly improve the mineralization of organic pollutants in wastewater. The use of iron-based catalysts not only improves the efficiency of sewage treatment, but is also favored for its stability and reusability, green and non-secondary pollution characteristics, and low operating costs.
[0004] However, catalyst powder technology faces some challenges in practical applications. First, powdered catalysts are difficult to recycle in industrial applications. When used in fixed bed reactors, the pressure drop problem may cause pipe blockage or even safety hazards; in fluidized bed reactors, the separation and recovery of catalysts also face challenges. The difficulty in recycling limits the widespread application of powdered catalysts in industry, especially in continuous flow reactions. Secondly, the working conditions of environmentally friendly catalysts are extremely unstable, requiring them to have high chemical, mechanical and thermal stability and to be able to work effectively in harsh environments that change dramatically at any time. However, the existing powdered catalysts have high requirements for the use environment, a narrow pH range for the environment, and are prone to reduced catalytic efficiency or even failure. These requirements pose higher challenges to catalyst powder technology.
[0005] In summary, although catalyst powder technology shows potential in the removal of antibiotics from water, in order to achieve its widespread application in industry, it still needs to overcome the problems of difficult recycling and high requirements for the use environment. Summary of the invention
[0006] The present application provides a magnetic catalyst for degrading antibiotics with wide pH adaptability and a preparation method thereof, aiming to solve the problems of difficult recovery of existing catalyst powders and narrow applicable pH range.
[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0008] In a first aspect of the present application, a method for preparing a magnetic catalyst for degrading antibiotics having a wide pH adaptability is provided, comprising:
[0009] S1, reacting a nickel salt with 2-methylimidazole in a solvent to obtain a nickel precursor;
[0010] S2, reacting a nickel precursor, a cobalt salt, polyvinyl pyrrolidone and dimethylimidazole in a solvent, collecting and drying the solid phase to obtain a cobalt-nickel bimetallic MOF;
[0011] S3, heat-treating the cobalt-nickel bimetallic MOF in argon gas to obtain.
[0012] Preferably, the nickel salt includes any one of nickel nitrate hexahydrate, nickel chloride hexahydrate or nickel sulfate hexahydrate.
[0013] Preferably, the cobalt salt includes any one of cobalt nitrate hexahydrate, cobalt chloride and its hydrate or cobalt sulfate heptahydrate.
[0014] Preferably, the molar ratio of the 2-methylimidazole to the nickel salt is (2-8):1.
[0015] Preferably, the mass ratio of the nickel precursor to polyvinyl pyrrolidone is 1:(5-10);
[0016] The mass ratio of the cobalt salt to the nickel precursor is (2-16):1;
[0017] The molar ratio of the dimethylimidazole to the cobalt salt is (2-8):1.
[0018] Preferably, the heat treatment is specifically as follows: heating to 700-900° C. at a heating rate of 2-10° C. / min, keeping the temperature for 2-4 hours; and then cooling to room temperature at a cooling rate of 2-6° C. / min.
[0019] Preferably, the solvent includes any one of methanol, ethanol or water;
[0020] In S1 and S2, the reaction temperature is room temperature.
[0021] The second aspect of the present application provides a magnetic catalyst for degrading antibiotics having a wide pH adaptability prepared by the above preparation method.
[0022] The third aspect of the present application provides the use of the above-mentioned magnetic catalyst for degrading antibiotics with wide pH adaptability to degrade antibiotics in water.
[0023] The fourth aspect of the present application provides a method for degrading antibiotics in water, wherein the antibiotics in water are degraded by using the above-mentioned magnetic catalyst for degrading antibiotics to catalyze the reaction between the oxidant and the antibiotic molecules.
[0024] Compared with the prior art, the beneficial effects of this application are:
[0025] The present invention introduces Ni element into Co metal organic framework (MOF) material and forms a carbon protective layer by high temperature heat treatment method to obtain a catalyst with high catalytic activity, good stability in a wide pH range and easy separation. Its preparation process is simple, safe and suitable for large-scale industrial production.
[0026] This application pre-synthesizes the precursor powder of Ni and dimethylimidazole, and then attaches ZIF-67 to the surface of the powder to generate a MOF structure, thereby introducing the Co and Ni bimetallics and maintaining the integrity of the MOF structure, and giving the material magnetism, which has high catalytic activity and is easy to separate. At the same time, the simultaneous presence of the two metals Co and Ni not only plays a synergistic role, improving the efficiency of catalytic degradation of pollutants, but also brings more non-radical degradation pathways, including stronger electron transfer ability and singlet oxygen generation ability, which not only has stronger catalytic activity, but also has universal applicability to various antibiotics in water bodies.
[0027] The present application heat-treats MOF under argon conditions to retain its surface porous structure while forming a carbon protective layer. On the one hand, it can improve the stability of the catalyst in a wide pH range, effectively reduce the interaction barrier between antibiotics in sewage and the catalyst interface, and enhance the catalytic degradation of antibiotics; on the other hand, it can increase the dispersion of the catalyst in sewage, prevent the catalyst from aggregating and deactivating, and thus effectively improve the degradation effect of antibiotics in sewage. In addition, by heat treatment, part of the Co and Ni elements are converted into magnetic oxide forms, further improving the magnetism of the catalyst and making it easy to separate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a process flow chart of the preparation of a magnetic catalyst for degrading antibiotics with wide pH adaptability in this application;
[0030] Figure 2 are SEM images of various catalysts before heat treatment;
[0031] Figure 3 are SEM images of various catalysts after heat treatment;
[0032] Figure 4 The figure shows the test results of tetracycline degradation by different catalysts;
[0033] Figure 5 The figure shows the test results of tetracycline degradation by different catalysts;
[0034] Figure 6 The test results of tetracycline degradation by NCCP / PMS system under different pH conditions are shown;
[0035] Figure 7 The figure shows the test results of tetracycline degradation by different degradation systems;
[0036] Figure 8 The figure shows the test results of the degradation of different antibiotics by the NCCP / PMS system;
[0037] Fig. 9 This is a physical picture of the magnet separation of catalyst NCCP;
[0038] Fig.10 This is a test result diagram of the cyclic removal performance of tetracycline by the NCCP / PMS system;
[0039] Fig.11 This is the SEM image of the catalyst NCCP after 8 cycles of testing. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0041] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0042] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0043] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0044] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0045] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0046] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0047] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0048] In the first aspect, the present application provides a method for preparing a magnetic catalyst for degrading antibiotics with wide pH adaptability, the process flow of which is as follows: Figure 1 As shown, including:
[0049] S1, reacting a nickel salt with 2-methylimidazole in a solvent to obtain a nickel precursor;
[0050] In the present application, the nickel salt may be any one of nickel nitrate hexahydrate, nickel chloride hexahydrate or nickel sulfate hexahydrate, preferably nickel nitrate hexahydrate; the solvent includes any one of methanol, ethanol or water, preferably methanol.
[0051] In the present application, the molar ratio of 2-methylimidazole to nickel salt is (2-8): 1, preferably 5: 1. The nickel salt and 2-methylimidazole are stirred in a solvent at room temperature for 24-36 hours, and the obtained solid is washed with methanol after the reaction and dried at 60° C. for 8 hours to obtain a nickel precursor.
[0052] S2, reacting a nickel precursor, a cobalt salt, polyvinyl pyrrolidone and dimethylimidazole in a solvent, collecting and drying the solid phase to obtain a cobalt-nickel bimetallic MOF;
[0053] In the present application, the cobalt salt includes any one of cobalt nitrate hexahydrate, cobalt chloride and its hydrate or cobalt sulfate heptahydrate, preferably cobalt nitrate hexahydrate; the solvent in this step is the same as the solvent in step S1.
[0054] In the present application, the mass ratio of the nickel precursor to polyvinyl pyrrolidone is 1:(5-10); the mass ratio of the cobalt salt to the nickel precursor is (2-16):1; the molar ratio of the dimethylimidazole to the cobalt salt is (2-8):1. The nickel precursor, polyvinyl pyrrolidone, cobalt salt and dimethylimidazole are stirred in a solvent at room temperature for 24-36 hours, the solid phase is collected by centrifugation, washed with methanol and dried at 60°C for 8 hours to obtain a cobalt-nickel bimetallic MOF.
[0055] This application uses cobalt-based imidazole (ZIF-67) containing active metal Co as the core, and the precursor powder of Ni and dimethylimidazole is pre-synthesized and then ZIF-67 is attached to the powder surface to continue to generate MOF structure, which realizes the introduction of Co and Ni bimetallics and maintains the MOF structure, while giving the material magnetism. The simultaneous presence of two metals, Co and Ni, not only plays a synergistic role and improves the efficiency of catalytic degradation of pollutants, but also brings more non-radical degradation pathways, including stronger electron transfer ability and singlet oxygen generation ability, with stronger catalytic activity. Compared with the free radical degradation pathways (sulfate radicals, hydroxyl radicals, superoxide radicals) of iron-based catalysts, it can catalyze and degrade all macromolecular pollutants (such as antibiotics and dyes) in water, and has higher universality.
[0056] S3, heat-treating the cobalt-nickel bimetallic MOF in argon gas to obtain.
[0057] In the present application, the cobalt-nickel bimetallic MOF is heated to 700-900°C at a heating rate of 2-10°C / min, and kept warm for 2-4 hours; then cooled to room temperature at a cooling rate of 2-6°C / min. By heat treating the cobalt-nickel bimetallic MOF under argon conditions, a carbon protective layer is formed while its surface porous structure is retained. The porous structure improves the catalytic effect of the catalyst, and the carbon protective layer makes the catalyst active in both acidic and alkaline environments, and can be used in a wide pH range;
[0058] In the present application, part of the Co and Ni elements are converted into magnetic oxide forms by heat treatment, which further improves the magnetism of the catalyst and makes it easy to separate, and can be separated by a magnet.
[0059] The present invention introduces Ni element into Co metal organic framework (MOF) material and forms a carbon protective layer by high temperature heat treatment method to obtain a catalyst with high catalytic activity, good stability in a wide pH range and easy separation. Its preparation process is simple, safe and suitable for large-scale industrial production.
[0060] The magnetic catalyst for degrading antibiotics prepared in the present application has better catalytic effect, safety and good environmental adaptability, and can be used to degrade antibiotics in water bodies. The magnetic catalyst for degrading antibiotics in the present application catalyzes oxidants, such as peroxymonosulfate, such as sodium peroxymonosulfate, potassium peroxymonosulfate, etc., to catalyze and degrade macromolecular pollutants such as dyes and antibiotics in water bodies, and has good universality. It has high degradation efficiency, low residual amounts of various antibiotics in the treated sewage, and will not cause harm to operators during the treatment process.
[0061] The catalyst catalytic oxidant of the present application, such as peroxymonosulfate PMS, has the following principles:
[0062] The principle of catalyst catalyzing PMS to produce free radicals: When activating PMS, the cobalt-nickel bimetallic catalyst powder mainly produces free radicals through two mechanisms. For the transition metal catalytic mechanism, the transition metals (Co and Ni) in the cobalt-nickel bimetallic catalyst powder can act as catalysts to promote the breaking of peroxide bonds (OO) in PMS molecules by providing or accepting electrons, generating highly active sulfate radicals (SO 4·-). These free radicals have a high redox potential (E0 = 2.5-3.1V) and can effectively oxidize antibiotics in water. For heterogeneous catalytic mechanisms, cobalt-nickel bimetallic catalyst powder, as a heterogeneous catalyst, can adsorb PMS molecules on its surface and react with PMS through active sites on the catalyst surface (such as metal ions or defect sites) to produce sulfate radicals. In addition, hydroxyl radicals (·OH) can also be generated on the catalyst surface. These free radicals are also highly oxidizing and can attack and degrade antibiotic molecules.
[0063] The principle of the catalyst catalyzing PMS to produce non-free radicals: In addition to the free radical pathway, the combination of cobalt-nickel bimetallic catalyst powder and PMS can also degrade antibiotics through non-free radical pathways. For the electron transfer mechanism, the cobalt-nickel bimetallic catalyst powder can directly transfer electrons with PMS to form metastable active substances (such as cobalt-nickel bimetallic catalyst powder-PMS complexes). These complexes can directly undergo oxidation reactions with antibiotic molecules to achieve degradation. For the singlet oxygen generation mechanism, the cobalt-nickel bimetallic catalyst powder produces highly active species such as singlet oxygen ( 1 O 2 ), these non-free radical active substances can also effectively degrade antibiotics.
[0064] Principles of free radical and non-free radical degradation of antibiotics: For free radical oxidation, free radicals (such as SO 4 ·- and ·OH) can directly attack antibiotic molecules, break chemical bonds such as CH, CC, CN in antibiotic molecules through oxidation, or change the molecular structure through addition reaction, thereby achieving the degradation of antibiotics. For non-radical oxidation, the active substances produced by non-radical pathways (such as 1 O 2 ) can react with antibiotic molecules through energy transfer, leading to oxidation or structural changes of antibiotic molecules, and then achieving degradation. Therefore, compared with free radical catalysis, non-free radical catalysis does not require the structure of the degraded product and has the characteristics of universality.
[0065] The present application is further described below by way of examples.
[0066] Example 1
[0067] This embodiment provides a method for preparing a magnetic catalyst for degrading antibiotics with wide pH adaptability, comprising:
[0068] S1, add 30 mmol of 2-methylimidazole and 6 mmol of nickel nitrate hexahydrate into 80 mL of methanol and stir to react for 24 hours. After the reaction is completed, collect the solid powder, wash it three times with methanol, and dry it at 60°C for 8 hours to obtain a nickel precursor powder;
[0069] S2, take 200ml of methanol solution and put it in a bottle, add 0.2g of nickel precursor powder, stir at room temperature for 20min to disperse evenly; then add 1.89g of polyvinyl pyrrolidone, stir to dissolve; then add 10mmol of cobalt nitrate hexahydrate and 40mmol of dimethylimidazole, stir at room temperature for 24h. Collect the solid phase by centrifugation, wash it three times with methanol, and dry it at 60℃ for 8h to obtain cobalt-nickel bimetallic MOF;
[0070] S3, heating the cobalt-nickel bimetallic MOF to 800°C in a high-temperature tube furnace at a heating rate of 2°C / min, keeping the temperature for 2h, and then cooling it to room temperature at a rate of 5°C / min to obtain the catalyst prepared in Example 1, denoted as Ni@Co-CNP-0.2.
[0071] Example 2
[0072] The difference between Example 2 and Example 1 is that the amount of nickel precursor powder used is 0.25 g, and the rest is the same as Example 1. The catalyst prepared in Example 2 is recorded as Ni@Co-CNP-0.25.
[0073] Example 3
[0074] The difference between Example 3 and Example 1 is that the amount of nickel precursor powder used is 0.3 g, and the rest is the same as Example 1. The catalyst prepared in Example 3 is recorded as Ni@Co-CNP-0.3.
[0075] Example 4
[0076] The difference between Example 4 and Example 1 is that the amount of nickel precursor powder used is 0.35 g, and the rest is the same as Example 1. The catalyst prepared in Example 4 is recorded as Ni@Co-CNP-0.35.
[0077] Comparative Example 1
[0078] Comparative Example 1 provides a method for preparing cobalt-based imidazole ZIF-67, comprising:
[0079] S1, add 30 mmol of 2-methylimidazole and 6 mmol of cobalt nitrate hexahydrate into 80 mL of methanol and stir to react for 24 hours. After the reaction, collect the solid powder, wash it three times with methanol, and dry it at 60 ° C for 8 hours to obtain cobalt-based ZIF;
[0080] S2, heating the cobalt-based ZIF in a high-temperature tube furnace to 800°C at a heating rate of 2°C / min, keeping the temperature for 2h, and then cooling it to room temperature at a rate of 5°C / min to obtain Co-CNP.
[0081] Comparative Example 2
[0082] Comparative Example 2 provides a method for preparing nickel-based imidazole ZIF-67, comprising:
[0083] S1, add 30 mmol of 2-methylimidazole and 6 mmol of nickel nitrate hexahydrate into 80 mL of methanol and stir to react for 24 hours. After the reaction is completed, collect the solid powder, wash it three times with methanol, and dry it at 60°C for 8 hours to obtain a nickel precursor powder;
[0084] S2, heating the nickel precursor powder to 800°C in a high temperature tube furnace at a heating rate of 2°C / min, keeping the temperature for 2h, and then cooling it to room temperature at a rate of 5°C / min to obtain Ni-CNP.
[0085] The catalysts before heat treatment (the product obtained in step S2) and the catalysts after heat treatment (the product obtained in step 3) in Examples 1-4 and Comparative Example 1 were respectively subjected to SEM tests to observe their microstructures.
[0086] Among them, the SEM image of the catalyst before the above heat treatment is as follows Figure 2 As shown, Figure a is the SEM spectrum of the catalyst Co-CNP of Comparative Example 1, and Figures b-e are the SEM spectra of the catalysts prepared in Examples 1-4, respectively. Figure 2 It can be seen that compared with the cobalt-based imidazole ZIF-67 without the addition of nickel precursor powder in comparative example 1, the particle volume of the samples after the addition of nickel precursor powder in examples 1-4 is reduced from 600-800nm to 400-500nm, and the morphology of cobalt-based imidazole ZIF-67 is maintained. The reduction in volume increases the specific surface area of the sample, thereby enhancing the adsorption capacity of pollutants.
[0087] The SEM images of the catalyst after the heat treatment are shown in Figure 3 As shown, Figure a is the SEM spectrum of the catalyst of Comparative Example 1, and Figures b-e are the SEM spectra of the catalysts prepared in Examples 1-4, respectively. Figure 3It can be seen that when no nickel is introduced, the powder basically maintains the original ZIF-67 structure; when 0.2g of nickel precursor is added, the powder's morphology is basically retained compared to before carbonization; when 0.25g is added, the edges and corners of the powder begin to curl and deform to a certain extent; when the amount of nickel precursor added is increased to 0.3g, the powder surface after carbonization shows obvious curling; and when the amount of addition is further increased to 0.35g, the powder is obviously curled compared to before carbonization, and the morphology structure is significantly changed. This shows that with the increase in the amount of nickel introduced, the morphology structure of the material will gradually be destroyed after high-temperature heat treatment, resulting in a decrease in catalytic activity.
[0088] The catalysts prepared in Examples 1-4 and Comparative Example 1 were tested for tetracycline degradation performance, and the test method was as follows:
[0089] 10 mg of catalyst powder and 10 mg of peroxymonosulfate (PMS) were added to 50 mL of 20 mg / L neutral tetracycline aqueous solution, and the removal rate of tetracycline was tested after 20 minutes of degradation. The removal rate was calculated as C t / C 0 *100%, of which C t is the concentration of tetracycline after degradation time t, C 0 is the initial concentration of tetracycline before degradation.
[0090] Test results such as Figure 4 As shown. Figure 4 As shown in Figure a, the effect of the catalyst is significantly enhanced after the introduction of nickel into the catalyst. When the amount of nickel precursor added is 0g, 0.2g, 0.25g, 0.3g and 0.35g, after 20 minutes of treatment, the removal rates of tetracycline in water are 83.6%, 95.8%, 97.0%, 94.6% and 92.6%, respectively. Figure 4 Figure b shows the removal rate constant k of the above catalyst powder when removing tetracycline. When the amount of nickel precursor added is 0g, 0.2g, 0.25g, 0.3g, and 0.35g, the k values are 0.25822min -1 、0.31096min -1 、0.25447min -1 、0.21795min -1 、0.14593min -1 This shows that the addition of nickel will improve the performance of the catalyst, but when too much nickel is added, the performance will be reduced to a certain extent due to the destruction of the morphology and structure of the material after high-temperature heat treatment. Therefore, 0.25g of nickel precursor is selected.
[0091] Example 5
[0092] The difference between Example 5 and Example 2 is that the heat treatment temperature is changed to 600° C., and the rest is the same as Example 2.
[0093] Example 6
[0094] The difference between Example 6 and Example 2 is that the heat treatment temperature is changed to 700° C., and the rest is the same as Example 2.
[0095] Example 8
[0096] The difference between Example 8 and Example 2 is that the heat treatment temperature is changed to 900° C., and the rest is the same as Example 2.
[0097] The catalysts prepared in Example 2 and Examples 5-8 were tested for tetracycline degradation performance, and the test method was as follows:
[0098] 10 mg of catalyst powder and 10 mg of peroxymonosulfate (PMS) were added to 50 mL of 20 mg / L neutral tetracycline aqueous solution, and the removal rate of tetracycline was tested after 20 minutes of degradation. The removal rate was calculated as C t / C 0 *100%, of which C t is the concentration of tetracycline after degradation time t, C 0 is the initial concentration of tetracycline before degradation.
[0099] Test results such as Figure 5 As shown. Figure 5 As shown in Figure a, the effect of the catalyst will change with the change of heat treatment temperature. When the heat treatment temperature is 600℃, 700℃ and 800℃, the removal rate of tetracycline in water gradually increases with the increase of temperature, which are 86.3%, 95.1% and 97.1% respectively. When the temperature increases to 900℃, the removal rate of tetracycline by the catalyst decreases to 92.7%. Figure 5 Figure b shows the removal rate constant k of the above catalyst powder when removing tetracycline. When the nickel heat treatment temperature is 600℃, 700℃, 800℃, and 900℃, the k value is 0.16552min, respectively. -1 、0.24753min -1 、0.31770min -1 、0.21795min -1 、0.22685min -1 This shows that the heat treatment temperature will affect the performance of the catalyst. Too high or too low a temperature will lead to a decrease in catalyst performance. This may be because when the temperature is low, there are fewer graphene structures in the material and the material has lower electron transport performance; and too high a temperature will cause certain damage to the structure. 800℃ is the optimal heat treatment temperature.
[0100] In the present application, when the amount of nickel precursor added is 0.25 g and the heat treatment temperature is 800° C., the prepared catalyst has the best catalytic effect, that is, the catalyst prepared in Example 2 has the best catalytic effect, and the catalyst prepared in Example 2 is recorded as NCCP.
[0101] The catalyst NCCP prepared in Example 2 was subjected to a tetracycline degradation test under different pH conditions. The removal rate was calculated as follows: t / C 0 *100%, of which C t is the concentration of tetracycline after degradation time t, C 0 is the initial concentration of tetracycline before degradation.
[0102] The test conditions are: oxidant PMS concentration is 300ppm, NCCP concentration is 300ppm, tetracycline TC concentration is 20ppm, and the test pH is 3-11. The test results are as follows Figure 6 As shown, the TC removal efficiency is the best at pH 7, reaching 96.8%; when the pH value increases to 9 and 11, the TC removal rate gradually decreases to 87.5% and 85.9%, respectively; when the pH value decreases to 5 and 3, the TC removal rate gradually decreases to 93.2% and 90.3%, respectively. This shows that the NCCP / PMS system of the present application performs best under neutral pH conditions, and due to the protective effect of the outer carbon layer, it also exhibits excellent TC removal performance in acidic and alkaline environments.
[0103] In order to further verify the degradation effect of the catalyst NCCP prepared in Example 2 on tetracycline, four groups of comparative experiments were set up for comparison, in which the concentration of tetracycline TC in the test solution was 20 ppm and the pH was 7. The calculation method of the removal rate is C t / C 0 *100%, of which C t is the concentration of tetracycline after degradation time t, C 0 is the initial concentration of tetracycline before degradation.
[0104] The experimental group used NCCP / PMS to degrade tetracycline, the comparison group 1 used PMS alone, the comparison group 2 used NCCP alone, the comparison group 3 used Co-CNP / PMS, and the comparison group 4 used Ni-CNP / PMS to degrade tetracycline. The PMS concentration was 300ppm, and the concentrations of NCCP, Co-CNP, and Ni-CNP were all 300ppm. The test results are as follows: Figure 7 As shown. Figure 7It can be seen that PMS alone has almost no ability to remove TC. After 20 minutes of reaction, the removal rate of tetracycline is only 7.0%. However, due to its porous structure, NCCP alone has an adsorption capacity for TC and can remove 55.7% of pollutants. The removal rates of tetracycline by NCCP / PMS, Co-CNP / PMS and Ni-CNP / PMS systems are 98.7%, 92.0% and 82.8%, respectively. Compared with other control groups, the NCCP / PMS system has a significantly higher tetracycline removal performance than other systems, indicating that the bimetallic catalyst prepared in the present invention has the best performance.
[0105] The degradation effect of the catalyst NCCP prepared in Example 2 on different antibiotics was tested in the following manner: the concentration of the oxidant PMS was 300ppm, the concentration of the NCCP was 300ppm, and the pH was 7; the antibiotics were selected as tetracycline (TC), ciprofloxacin (CIP), levofloxacin (LFX), and sulfamethoxazole (SMX) at a concentration of 20ppm, and rhodamine B (RhB) at a concentration of 100ppm. The removal rate was calculated as follows: t / C 0 *100%, of which C t is the concentration of antibiotic after degradation time t, C 0 is the initial concentration of antibiotic before degradation.
[0106] Test results such as Figure 8 As shown. Figure 8 It can be seen that after 20 minutes of reaction, the removal rates of tetracycline, ciprofloxacin, levofloxacin, sulfamethoxazole and rhodamine B are 98.4%, 93.5%, 93.8%, 96.9% and 99.7% respectively. The test results show that NCCP has excellent removal performance for various antibiotics and dyes.
[0107] The cyclic performance of the catalyst prepared in Example 2 was tested. The specific test method was as follows: under the conditions of 300ppm PMS concentration of the oxidant, 300ppm catalyst concentration, 20ppm tetracycline TC concentration, and pH 7, after 20 minutes of tetracycline removal, the powder was recovered by magnet adsorption, washed 3 times with anhydrous ethanol, and dried at 60°C for 30 minutes before the next removal test, and a total of 8 cycles were performed. The test results are as follows: Fig. 9 , Fig.10 and Fig.11 shown.
[0108] Fig. 9 This is a test diagram of the magnetic adsorption and recovery of catalyst powder. It can be observed that the catalyst powder has strong magnetism and can be easily adsorbed and collected by the magnet, and the powder can still be collected in clusters after leaving the magnet. Fig.10The cyclic removal performance of tetracycline by the NCCP / PMS system is shown. After 8 reactions of 20 minutes each, the removal rates of tetracycline are 98.4%, 98.1%, 96.4%, 95.7%, 94.7%, 94.5%, 94.3% and 94.5%, respectively. The removal rate of tetracycline is always maintained above 90%, indicating that the catalyst of the present application has excellent cyclic use performance.
[0109] Fig.11 This is the SEM image of the catalyst after 8 cycles of testing. After multiple cycles of testing, the surface morphology of the material has hardly changed. The tiny particles on its surface may be caused by the adsorbed tetracycline.
[0110] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a magnetic catalyst for degrading antibiotics with wide pH adaptability, characterized in that: include: S1, reacting a nickel salt with 2-methylimidazole in a solvent to obtain a nickel precursor; S2, reacting a nickel precursor, a cobalt salt, polyvinyl pyrrolidone and dimethylimidazole in a solvent, collecting and drying the solid phase to obtain a cobalt-nickel bimetallic MOF; S3, heat-treating the cobalt-nickel bimetallic MOF in argon gas to obtain.
2. The preparation method according to claim 1, characterized in that: The nickel salt includes any one of nickel nitrate hexahydrate, nickel chloride hexahydrate or nickel sulfate hexahydrate.
3. The preparation method according to claim 1, characterized in that: The cobalt salt includes any one of cobalt nitrate hexahydrate, cobalt chloride and its hydrate or cobalt sulfate heptahydrate.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the 2-methylimidazole to the nickel salt is (2-8):
1.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the nickel precursor to polyvinyl pyrrolidone is 1:(5-10); The mass ratio of the cobalt salt to the nickel precursor is (2-16):1; The molar ratio of the dimethylimidazole to the cobalt salt is (2-8):
1.
6. The preparation method according to claim 1, characterized in that: The heat treatment is specifically as follows: heating to 700-900°C at a heating rate of 2-10°C / min, keeping the temperature for 2-4h; and then cooling to room temperature at a cooling rate of 2-6°C / min.
7. The preparation method according to claim 1, characterized in that: The solvent includes any one of methanol, ethanol or water; In S1 and S2, the reaction temperature is room temperature.
8. A magnetic catalyst for degrading antibiotics with broad pH adaptability prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the magnetic catalyst for degrading antibiotics with broad pH adaptability as claimed in claim 8 to degrade antibiotics in water.
10. A method for degrading antibiotics in water, characterized in that: The antibiotics in the water are degraded by using the magnetic catalyst for degrading antibiotics as claimed in claim 8 to catalyze the reaction between the oxidant and the antibiotic molecules.